Phase Composition and Structure of High Alloy Based on Ni-Al-Co; Mechanical Engineering, Automation and Control Systems (MEACS) - Kozlov E. Edward; Popova N. Natalya; Nikonenko E. L. Elena Leonidovna; Sizonenko N. Nina; Zboykova N. Nadezhda; Koneva N. Nina (2015, 2015)
Title screen